The study of aids morbidity in HIV-infected population and antiretroviral therapy effect - Грижак, Ігор Гнатович (ScienceRise: Medical Science, 2017)
Aim. To estimate AIDS morbidity dynamics in Ivano-Frankivsk region and the degree of its controllability by antiretroviral therapy existing incidence of HIV-infected people. Methods. We calculated the number of detected people living with HIV in Ivano-Frankivsk region = all identified HIV-infected people for the entire period of epidemiological observation – (dead HIV-positive people + people with removed diagnosis + people who left the region). We estimated HIV-infection annual transition in patients to AIDS stage (ATA = the number of new registered AIDS cases × 100 % / detected people who leaves with HIV), the incidence of HIV-people by antiretroviral therapy (IART), and Pearson correlation coefficient. The tendency of cerebral toxoplasmosis morbidity was determined automatically by least squares method using Excel program, and its prognosis was determined by extrapolation into the future. Results. It was found, that the identified 1661 HIV-positive people leaved in the region in 2015, but only 892 of them were under clinical observation (53.7%). ATA decreases from 9.1% in 2013 to 5.1% in 2015, but no reverse correlation between ATA and IART was found. IART was insufficient – 69.8% of people who was under the clinical observation, and 37.2% of all detected HIV-people. According to a growing tendency of cerebral toxoplasmosis morbidity, we expected 10 cases in 2016 and 11 in 2017. Conclusion. The incidence of HIV-people by antiretroviral therapy was insufficient, therefore, it did not have the preventive effect on AIDS and, particularly, on cerebral toxoplasmosis among HIV-people